2019
DOI: 10.3390/su11154141
|View full text |Cite
|
Sign up to set email alerts
|

External Financing, R&D Intensity, and Firm Value in Biotechnology Companies

Abstract: Focusing on biotechnology firms, this study analyzes the relationship between the level of intensity of the research and development (R&D) conducted by a firm, the debt financing decisions the firm makes, and the overall value of the firm. The data presented shows that, although most firms are unlikely to acquire financing from the debt market, the opposite is true for firms in the biotechnology industry. One reason for this divergence may be the belief among biotechnology firms that their future commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Rapidly growing firms tend to reinvest their earnings back into the firm instead of returning them to shareholders. Free cash flow for R & D intensive firms is entirely utilized for growth opportunities [73]; therefore, R & D intensive firms and biotech firms are less likely to distribute cash dividends to shareholders where R & D investment is always in urgent need. As seen in the results, however, if a firm has enough available cash, it is more likely to distribute cash dividends.…”
Section: Discussion-hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Rapidly growing firms tend to reinvest their earnings back into the firm instead of returning them to shareholders. Free cash flow for R & D intensive firms is entirely utilized for growth opportunities [73]; therefore, R & D intensive firms and biotech firms are less likely to distribute cash dividends to shareholders where R & D investment is always in urgent need. As seen in the results, however, if a firm has enough available cash, it is more likely to distribute cash dividends.…”
Section: Discussion-hypothesismentioning
confidence: 99%
“…Size, which is the natural log of total assets, is included here in order to control for side effects, and it may be positively correlated with market value. Leverage, which equals 1 if the value of total liabilities divided by total assets is above the median, may be negatively correlated with market value [73]. Sales growth controls for growth, and the market-to-book ratio is calculated by dividing the market value of equity by the book value.…”
Section: Regression Model and Measurement Of Variablesmentioning
confidence: 99%
“…Obtaining the data of R&D investments from the Compustat database, we then estimated the difference in R&D in year 0. In Equation ( 2), on the basis of [2,7,14,15,19], we defined this variable, and it was equal to the R&D expenditure in year 0 minus the R&D expenditure in year −1 and then divided by firm assets in year −1. Thus, the measurement of the dependent variable was expressed as follows:…”
Section: Dependent Variablementioning
confidence: 99%
“…The prior literature indicates that firms with sufficient funds to invest in research and development (R&D) can create sustainable development advantages and accumulate in-tangible assets [1][2][3][4]. This study aims to investigate the relationship between financial leverage and R&D investment.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Bostian et al [38], using plant-level production data for Swedish manufacturing firms, showed that environmental technology investments have a positive effect on the firm performance, measured by the productivity changes. Lee et al [39], on the case of Korean biotechnology firms, while examining the relationship between R&D intensity and firm value, found that total asset investments and asset tangibility have a positive effect on the firm value, measured by Tobin's Q.…”
Section: Literature Reviewmentioning
confidence: 99%